2017
DOI: 10.3233/cbm-160450
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-associated gigantomastia recurrence and ectopic breast after reduction mammaplasty: A case report

Abstract: It has been reported that majority of cases of gigantomastia, also known as breast hypertrophy and macromastia, occur during either pregnancy or puberty. Gigantomastia is a rare disorder that does not have a clear etiology or well-established risk factors. We present a 26-year-old female patient who appeared to have pregnancy-associated gigantomastia recurrence, large accessory breast and, ectopic breast tissue at external genital three years after bilateral breast reduction surgery. The patient successively u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
1
5
0
5
Order By: Relevance
“…The probable associated risk factors are described. The disease occurs in multiparous according to some authors [2, 4, 9], rarely in nulliparous women [11]; in our case study and as reported by other authors [5, 8], it occurs in the second gravidity. White race more involved in the literature, is more an observation than just a rational explanation [12].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The probable associated risk factors are described. The disease occurs in multiparous according to some authors [2, 4, 9], rarely in nulliparous women [11]; in our case study and as reported by other authors [5, 8], it occurs in the second gravidity. White race more involved in the literature, is more an observation than just a rational explanation [12].…”
Section: Discussionsupporting
confidence: 86%
“…The last impose an immediate [7] or differed [11] reconstruction according to the local conditions. However, reductive surgery exposes to risk of recurrence in some rare cases that have been described [5]. We opted for this plastic surgery on a patient who rejected bilateral mastectomy despite counseling concerning the risk of recurrence even though she did not desire future pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GG or gravida macromastia is defined as a disorder characterized by diffuse, extreme, and disabling enlargement of one or both breasts during pregnancy, which was first described in 1648 by Palmuth 1,2,6 . Its etiology is still unknown 1,7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…• Definition: Breast hyperplasia, presenting as large breasts, may unusually be problematic for a number of reasons including postural abnormalities, backache, psychological disturbance, and submammary intertrigo. The condition may occur at puberty (O'Hare and Frieden 2000) or during pregnancy (Parker et al 2017;Zhou et al 2017b;Shoma et al 2011). Its etiology is obscure, but a suggested cause is increased sensitivity of the breast tissue to normal levels of circulating hormones.…”
Section: Breast Hyperplasiamentioning
confidence: 99%